Enhancing professional practice : a framework for teaching - Danielson, Charlotte (Alexandria, VA : Association for Supervision and Curriculum Development, 2007)
Describes a framework for teaching based on the PRAXIS III criteria which identifies those aspects of a teacher's responsibilities that promote improved student learning; exploring twenty-two components, grouped into the four domains of planning and preparation, classroom environment, instruction, and professional responsibilities.
Includes bibliographical references (p. 193-195) and index.
Professional
Keywords: Classroom environment; Educational planning; Teaching; Classroom management; Teaching